Experimental Study of Vitiation Effects on Combustion Characteristics of a Supersonic Combustor. Issue 9 (2nd September 2017) - Wang, Yanhua; Song, Wenyan; Shi, Deyong; Fu, Qiang; Wang, Yuhang
ABSTRACT: An experimental study was conducted to characterize the effects of vitiate species (H2 O and CO2 ) on supersonic combustion. These species were added to an initially clean airflow that was supplied by an electrically heated direct-connected facility. Wall pressures were measured by pressure sensors, combined with combustion optical images, and the influence of major vitiate species (H2 O and CO2 ) on supersonic combustion was analyzed. Experimental results showed that the presence of vitiate species decreased combustor pressures by 3% to 30% for the same fuel equivalence ratio. The combustion flame images indicated that the flame-spreading angle decreased with the increase of the molar fraction of H2 O and CO2, and when the molar fraction of CO2 was increased to 3.5%, an illogical oscillation, specifically embodying as the flame round switching between the upstream cavity and the downstream cavity, could be observed in the combustion, which might possibly cause the flame extinction.